The culture of learning in Khayelitsha secondary schools: teachers' perspectives - Pager, Devah Iwalani (Department of Sociology, 2023)
This research project focused on teachers' perspectives on improving the culture of learning in their schools. The 'culture of learning' is a term which has achieved widespread popular usage, serving as a catch phrase to describe the overall crisis in education. Broadly defined, the 'culture of learning' refers to the attitudes and behaviors demonstrated by members of a school which foster a particular orientation towards learning. This culture is critical to the educational success of students, who must be motivated before learning can occur. Within South Africa, the culture of learning has largely disintegrated in African schools. This project seeks to gain a better understanding of the culture itself as well as to identify strategies for its improvement. The 'culture of learning' is a term which has received little or no critical analysis in the South African education literature, despite its frequent use. The first part of this thesis locates the culture of learning within a theoretical context, using international literature of school cultures which promote negative attitudes towards learning. Additionally, the history of South African education is reviewed to trace the events which may have contributed to the erosion of the culture of learning in African schools. On the basis of these theoretical and historical accounts, I conclude that structural inequality is fundamental to the deterioration of the culture of learning. Once these structural inequalities are resolved, however, the restoration of a learning culture does not necessarily follow. Instead, direct school-level interventions are necessary to facilitate changes in the attitudes and behaviors of students and teachers. This thesis does not attempt to provide an overall analysis of the culture of learning but focuses on the perceptions of one group of people: teachers. Teachers from four Khayelitsha schools were included in this study. A combination of qualitative and quantitative data was gathered, with 23 teachers participating in in-depth interviews and 56 teachers filling out questionnaires. All participation was solicited on a voluntary basis. Teachers' perspectives on how to improve the culture of learning in their schools covered a wide range of issues. While both material resources and human resources were considered highly important to the restoration of a learning culture, teachers overwhelmingly stressed the importance of human resources, including the motivation of students and teachers. According to respondents, the motivation of students, the defining feature of the culture of learning, is highly contingent on · the motivation level of teachers. In this respect, the 'culture of teaching' is the critical component of the broader 'culture of learning' and one which warrants serious attention. The low motivation and morale of teachers can be indirectly measured in many ways. Teachers reported high levels of absenteeism, truancy, 'laziness', substance abuse and subversion of assessments, as well as the frequency of leaving the profession, as signs of low motivation among their peers. Teachers offered varied explanations for this phenomenon, including the historical degradation of teaching as well as the present dilapidated conditions in schools. A number of strategies for improving teacher motivation were offered by respondents, ranging from improved working conditions to stricter discipline. The most commonly discussed strategy was an increase and improvement in the provision of in-service training and workshops for teachers. According to teachers, workshops would serve both to increase the skills of teachers as well as to provide a forum in which to support one another and revive their interest in the profession. If in-service activities are planned and implemented with active participation and guidance from teachers, the process can serve not only to reform current teaching behaviors but also to transform attitudes and capacities towards future upgrading. Based on the present findings, a participatory and democratic approach to all levels of education decision-making is recommended. Teachers' views of the culture of learning do not mesh neatly with the understanding that underlies current policy initiatives. Major national and provincial policy to date has focused primarily on the organizational and administrative issues central to the restructuring of the national education system. These policies have not yet addressed school-level concerns beyond ideological commentaries. The major initiative focusing on comprehensive school-level reform, the RDP Culture of Learning Programme, has focused almost exclusively on the physical renovation of schools. If teachers are right, these material improvements will have little long-term effect on the overall culture of learning. The emphasis must be placed, instead, on human resource issues, namely, the upgrading and encouragement of teachers.